PENINGKATAN KINERJA MEMBRAN SELULOSA ASETAT UNTUK PENGOLAHAN AIR PAYAU DENGAN MODIFIKASI PENAMBAHAN ADITIF DAN PEMANASAN - Joko Supriyadi; Dhias Cahya Hakika; Tutuk D. Kusworo (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Membrane is an alternative technology to the water treatment filtration principle that is being widely developed. A common type of polymer used in the manufacture of membranes are cellulose acetate. Sometimes aditive addition used to improve the morphology structure of membrane. The purpose of this research is to make an asymmetric membrane using cellulose acetate polymer additives as well as assess the effect of heating on the structure and morphology and performance of cellulose acetate membranes in brackish water treatment. Research making of cellulose acetate membranes for brackish water treatment is done with the variation of PEG concentration of 1, 3, and 5% by weight and the temperature and time of annealing at 600C and 700C for 5, 10, and 15 seconds. Membrane characterization consists of calculation membrane flux and rejection with brackish water as a feed, SEM, and FTIR analysis. From the research it can concluded that asymmetric cellulose acetate membrane can made by dry/wet phase inversion method. The more added concentration of PEG, the larger pore of membrane. Meanwhile the higher temperature and the longer time of annealing treatment, the skin layer of membrane become denser. Membrane with the composition of 18% cellulose acetate, 5% PEG, 1% distilled water, with heat treatment at temperature of 700C for 15 seconds is obtained optimal performance: flux  6.52 L.M-2.h-1.bar-1, 71% of TDS rejection, 63.75% of turbidity rejection, 52.9% rejection of Ca2+, and 41.9% rejection of Mg2+.